2020
DOI: 10.1186/s13102-020-00221-9
|View full text |Cite
|
Sign up to set email alerts
|

Warm-up durations in a hot-dry climate affect thermoregulation, mean power-output and fatigue, but not peak power in specific soccer repeated-sprint ability

Abstract: Background This study addressed the lack of data on the effect of warm-up (WU) duration in hot-dry climate (~ 30 °C; ~ 18% RH), on thermoregulation, muscular power-output, and fatigue after specific soccer repeated-sprint test (RSA). Methods Eleven amateur soccer players participated in a cross-over randomized study and they underwent the Bangsbo repeated-sprint test, after three WU durations (i.e. WU10, WU15 and WU20 min) at 70% of MAV, and on dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…This increase was shown to be a major factor responsible for improving nerve conduction velocity, enzymatic activities, oxygen delivery to muscles as well as for decreasing muscular viscous resistance [56]. Similarly, an increase in muscle temperature was shown to be responsible for a ~4% improvement of muscular leg power for each elevated 1˚C [54].…”
Section: Comparison Between the Nc Vs Qsc Conditionsmentioning
confidence: 95%
See 2 more Smart Citations
“…This increase was shown to be a major factor responsible for improving nerve conduction velocity, enzymatic activities, oxygen delivery to muscles as well as for decreasing muscular viscous resistance [56]. Similarly, an increase in muscle temperature was shown to be responsible for a ~4% improvement of muscular leg power for each elevated 1˚C [54].…”
Section: Comparison Between the Nc Vs Qsc Conditionsmentioning
confidence: 95%
“…Moreover, Yamaguchi et al [53] reported Pmax in HOT (35˚C) 3% higher than in NC (20˚C). Frikha et al [54] noted that the higher mean power-output values in HOT (30˚C) conditions may be related to the higher increase in core temperature [55]. This increase was shown to be a major factor responsible for improving nerve conduction velocity, enzymatic activities, oxygen delivery to muscles as well as for decreasing muscular viscous resistance [56].…”
Section: Comparison Between the Nc Vs Qsc Conditionsmentioning
confidence: 99%
See 1 more Smart Citation